(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
The reconstruction of the existing industrial building with a steel frame was carried out due to the need to convert the premises into a warehouse in order to increase the volume of the building for the storage of medical goods. The current state of the issue is summarized, research tasks are set, and the methodologyfor assessing the technical condition of the building’s structures in use has been developed. The normative procedure for assessing the technical condition and load-bearing capacity of the operated structures during reconstruction and completion in order to increase the volume of the building and improve operational qualities has been adopted. A method of obtaining the determining parameters of the technical condition of structures has been developed. It is assumed that structures and elements during the entire life cycle as a result of aging, degradation and other actions and influences can consistently be in each of the four technical states according to the requirements of current regulatory documents. The results of the performed survey, computer modeling and assessment of the technical condition of the construction structures of the existing building are presented. On the basis of the calculations performed using the software complex of the finite element method, the forces in the elements of the computer model were determined, the necessary cross-sections of the elements of columns, trusses, spans, and connections were established. Manufacturing, transportation and installation of structures were also performed. The building after the reconstruction is a one-story frame structure consisting of column foundations rigidly connected to reinforced concrete structures, on which the covering structures rest. The connection of trusses with columns is hinged. The system of connections along the columns and covering ensures the spatial rigidity of the building. Strengthening of the foundations has been carried out. The thickness of the insulation of the enclosing structures is adopted in accordance with the requirements of current regulatory documents.